Self-identification issue in American fiction of 2000s - Rykova, Hanna (Studia Philologica, 2021)
The article focuses on the issue of self-identity search in the novels of two American authors such as David Ebersghoff with his “The Danish Girl” (2000) and Jeoffrey Eugenides with his “Middlesex” (2002). Identity transformation being one of the main categories of our research makes the process of identity shift together with the influence of space travels and gender blurring on it more vivid. This article logically continues a previously started research of the self-identity issue in American fiction. The identity process is a remarkable trait of social and cultural life of all the times and is still crucial for national and family identification. As a consequence another problem arises that is differentiation between the categories of gender and sex as well as the issue of self appreciation within your family and certain location / community. Yi-Fu Tuan’s space and place theory from the perspective of experience facilitates the approach to the analysis of body and space relationnship in the novels and creates a smooth background for transition from space and body issues into body and gender field. J. Butler’s gender theory together with H. Urbach’s theory of gender and space order serve the basis for the detailed investigation of various somatic codes’ functioning and interaction. The analysis has shown the way the so-called identificational chain fluctuates both in the somatic and spacial spheres and the way these spheres interact. As a result the main protagonists Einar Wegener and Cal Stephanidis’ gender roles together with the identity change to such an extent that they both come to understanding of being trapped in their body. And it’s important to say that the process of the identity fluctuation obtains dynamic and continuous character that constantly redefines gender identity borders. The formation of an integral (artistic or familial, national, cultural) space within the text facilitates the gender identity’s transition and provides additional instruments for a better identity performance. Key words: self-identity, gender identity, sex, space, travel / transition, migration.